Smear Positive Tuberculosis Cases in Rajshahi District A Comparison Between Rural and Urban Areas (TAJ: Journal of Teachers Association, 2009)
This study was designed to know the case finding of sputum smear positive tuberculosis in Rajshahi district and also to see whether case finding was different in urban and rural settings. Our study reveals that case finding rate of smear positive tuberculosis cases in the city corporation area and rural areas of Rajshahi district are 52% and 28% respectively. Case detection rate of total Rajshahi district was 33%. Stronger efforts are needed to reach the national target of detecting 70% new smear positive TB cases by the end of 2005.   doi: 10.3329/taj.v17i2.3456   TAJ 2004; 17(2): 104-105